Evaluating the Effectiveness of Correctional Education A Meta-Analysis of Programs That Provide Education to Incarcerated Adults - Davis, Lois M. (RAND Corporation, 2013)
After conducting a comprehensive literature search, the authors undertook a meta-analysis to examine the association between correctional education and reductions in recidivism, improvements in employment after release from prison, and other outcomes. The study finds that receiving correctional education while incarcerated reduces inmates' risk of recidivating and may improve their odds of obtaining employment after release from prison.